Temporal seizure focus and status epilepticus are associated with high-sensitive troponin I elevation after epileptic seizures - Chatzikonstantinou, Anastasios; Ebert, Anne; Hennerici, Michael G. (Epilepsy research, 2015)
Objective: Postictal elevation of high-sensitive troponin I (TNI), a highly specific biomarker for myocardial ischemia, has been reported. We aimed at evaluating its association of high-sensitive troponin I (TNI) with seizure type and focus, as well as vascular risk factors. Methods: TNI was measured in 247 patients admitted to our clinic via the emergency room with an acute epileptic seizure. TNI control measurements were performed in 61.5% of cases. All patients underwent electroencephalography and cerebral imaging. Seizure focus - when possible - was determined using results from these examinations as well as clinical data. Results: Of 247 patients, 133 (53.8%) were men, the mean age was 59±18 years. 70 (28.3%) patients had focal and 177 (71.7%) generalized seizures. Status epilepticus was present in 38 cases (15.4%). Mean TNI was 0.05±0.17. TNI was elevated in 27 patients (10.9%). Higher age, status epilepticus and temporal seizure focus were significantly associated with TNI elevation in multivariate analysis. In 21 (13.8%) of the patients with TNI control measurement, TNI was continuously elevated. Higher age and temporal seizure focus were significantly associated with continuously high TNI. Coronary heart disease and vascular risk factors were significantly associated with high TNI only in univariate analysis. No patient had a symptomatic myocardial ischemia. Discussion: Postictal TNI elevation is relatively common in older patients with status epilepticus or temporal seizure focus. These data support the concept of relevant and possibly dangerous ictal effects on cardiac function especially in temporal lobe seizures. Although the risk of manifest postictal myocardial infarction seems to be very low, selected patients could profit from closer monitoring.
Gesehen am 26.11.2018